Drivers of antimicrobial resistance within the communities of Nepal from One Health perspective: a scoping review - Parajuli, Ayuska; Mitchell, Jessica; King, Natalie; Arjyal, Abriti; Latham, Sophia; King, Rebecca; Baral, Sushil (Frontiers in Public Health, 2024)
Background: A major driver of antimicrobial resistance (AMR) is the inappropriate use of antimicrobials. At community level, people are often engaged in behaviors which drive AMR within human, animal and environmental (One Health) impacts. This scoping review consolidates research to determine:determine a) community's knowledge attitudes and practices around AMR b) existing community-based interventions c) barriers and enablers to addressing AMR in Nepal. Method: This scoping review follows the Joanna Briggs institute scoping review methodology. Literature indexed in PubMed, SCOPUS, CINAHL, Global Index Medicus, HINARI-SUMMON, EMBASE (Ovid), Global Health (Ovid), CAB Abstracts (Ovid), Web of Science and Google Scholar between January 2000 and January 2023 were reviewed for inclusion. Articles were included in the review if they considered the issues of AMR at the community level in Nepal, this excluded clinical and lab-based studies. 47 studies met these criteria, were extracted, and analyzed to consolidate the key themes.Result: 31 (66%) articles exclusively included human health, five (11%) concentrated only in animal health, no studies solely focused on environmental aspects of AMR and remaining studies jointly presented human, animal and environment. Findings revealed inadequate knowledge accompanied by inappropriate practice in both human and animal health sectors. Four community interventions improved knowledge and practices on appropriate use of antimicrobials among community members.However, various social and economic factors were found as barriers for appropriate use of antimicrobials in the community.Community engagement and one health approaches could be a key tool to improve awareness of AMR and promote behavioural change related to AM use in communities as current studies have revealed inadequate knowledge alongside inappropriate practices shared in both human and animal health sectors.